Bimbingan Perkawinan Calon Pengantin: Upaya Mewujudkan Ketahanan Keluarga Nasional - Arditya Prayogi; Muhammad Jauhari (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
This article with a literature study aims to describe the implementation of marriage guidance programs, as a pre-marital program which is expected to be a systematic way to realize national family resilience. Marriage is one of the sunnah of the Prophet Muhammad which is carried out as an effort to fulfill human biological needs to live together, love each other, love each other and love each other and contains a vertical dimension. The results of the discussion show that the realization of family resilience must start from the process of forming a family through legal marriage, according to religious values. The family is the main foundation in building a system and social order as the basis for national resilience. Marriage guidance is a form of revitalization to strengthen the formation of marriage institutions which is a concrete effort that is expected to be able to realize the formation of many sakinah families in Indonesia. The marriage guidance program is a form of state responsibility to be able to realize national family resilience.